2012
DOI: 10.1002/pc.22242
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of rubber composites reinforced by zinc methacrylate and carbon black

Abstract: Zinc methacrylate (ZMA) and carbon black (CB) are incorporated into natural rubber/butadiene rubber matrix by direct mixing in a Banbury mixer. Tensile and tear tests showed that CB has a great reinforcing effect on rubber matrix. The results show that the amount of ZMA also plays an important role in mechanical properties. The addition of ZMA resulted in a significant increase of the optimum cure time even at lower loading. Incorporation of ZMA improved mechanical properties, such as tensile modulus and cure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Few latest studies confirmed that there is a predicted possibility for an increment in the carbon black consumption by the rubber industries with the increased procurement of natural and synthetic rubber in the near future [3]. The reason for the continuous usage of carbon black in the rubber industries is mainly because of its ability to impart desirable properties such as tensile strength, modulus, hardness, and tear strength to the rubber matrix depending to the end application [4]. Even though with these many numbers of positive properties, still, carbon black holds some drawbacks to it and the most sounded one is its pollution-related issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few latest studies confirmed that there is a predicted possibility for an increment in the carbon black consumption by the rubber industries with the increased procurement of natural and synthetic rubber in the near future [3]. The reason for the continuous usage of carbon black in the rubber industries is mainly because of its ability to impart desirable properties such as tensile strength, modulus, hardness, and tear strength to the rubber matrix depending to the end application [4]. Even though with these many numbers of positive properties, still, carbon black holds some drawbacks to it and the most sounded one is its pollution-related issues.…”
Section: Introductionmentioning
confidence: 99%
“…Even though with these many numbers of positive properties, still, carbon black holds some drawbacks to it and the most sounded one is its pollution-related issues. Production, storage, and lifecycle of carbon black result in considerable emission of carbon dioxide which in turn increases the carbon footprint of particular rubber product and production method [4]. One kilogram of carbon black can produce two to three kilograms of carbon dioxide during its life cycle, and the usage of carbon black in rubber products can increase its carbon footprint and in turn make it less sustainable [3].…”
Section: Introductionmentioning
confidence: 99%
“…Here, a novel ionic crosslinker is developed by using two common fillers in the current rubber industry: bis­[3-(triethoxysilyl)­propyl]­tetrasulfide (TESPT) and zinc methacrylate (ZDMA). , This ionic crosslinker has demonstrated the capability to crosslink different types of unsaturated rubbers via building a fully reversible ionic crosslinked structure. Such ionic crosslinked styrene butadiene rubber (SBR) with good mechanical property can be transformed into linear rubber and dissolved in the mixed solvents of toluene and chloroacetic acid, which can be easily recycled by being poured the solution into alcohol, and the recycled SBR can be reprocessed by adding zinc oxide as a crosslinker.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, there are generally two methods of reinforcing rubber by zinc dimethacrylate, both domestically and abroad. One is adding zinc dimethacrylate prepared in advance to reinforce the rubber [6][7][8]. The other is adoption of an in-situ reaction from methacrylic acid and zinc oxide, thus generating in-situ zinc dimethacrylate during the mixing process [9][10][11].…”
Section: Introductionmentioning
confidence: 99%